Soborowe czyny żeńskich wspólnot zakonnych na przykładzie Zgromadzenia Córek Maryi Niepokalanej jedną z form przygotowań do milenium chrztu Polski w latach 1959-1966 - Agata Mirek (Wrocławski Przegląd Teologiczny)
In the years 1962–1965, the Second Vatican Council deliberated in Rome, convened by Pope John XXIII in order to modernize and renovate the Catholic Church. Polish communist government wanted to use the Council for its own use. Church in Poland, especially monastic orders, undertook many joint initiatives aimed to provide spiritual assistance of proceedings of Council’s fathers. In Poland, the council action was linked to the Great Novena programme before the millennial anniversary of the baptism of Poland celebrated throughout 1966. The Primate noticed the coincidence of the work and aims of the Council with the work and aims of the Great Novena. The objective of the Council was to renew the spirit in the Church accordingly to the needs of contemporary people, meanwhile the goal of the Great Novena was to renew and to reborn morally the nation on the verge of the second millennium of Christianity. The final outcome of the works was brave and enthusiastic undertaking of conciliar rebirth by the orders, as preparation for the celebration of millennium of the Christening of Poland, celebrated in 1966.